Fabrication and Study Structure and Optical Properties of Cu0.75Zn0.25S Thin Film - Soud, Ali J.; Al-Maiyaly, Bushra K.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Thin films (CuxZn1-xS) with x = 0.75 nano crystallized were deposited from the alloy on glass substrates in a vacuum 2 × 10− 5 mbar by thermal evaporation technique with 450±20 nm thickness. The effects of annealed temperature (deposits, 423, 523, and 623) K for one hour on the structure, morphology, and optical properties of Copper Zinc Sulfide (CZS) films were investigated. The structural properties of Cu0.75Zn0.25S films were examined using the X-ray diffraction (XRD) technique as a function of annealed temperatures. XRD presented the Cu0.75Zn0.25S films as polycrystalline in the environment by a mixed hexagonal structure of CuS-ZnS, preferred orientation along the (201) plane, and crystallite size varying from 8.41-23.28 nm with annealing temperature. Atomic force microscopy (AFM) analysis was used to investigate the morphological properties of Cu0.75Zn0.25S films; the grain size of these films varies with annealing temperature in the range of (58.39 to 139.42) nm with uniform distribution. The influences of annealing temperature on the optical characterization of Cu0.75Zn0.25S thin film were examined using UV-Vis absorption spectroscopy. Direct band gap values of Cu0.75Zn0.25S films are gained from optical absorption measurements with a range (2.3-1.8) eV as a function of annealing temperature. From the results obtained above, it appears to us that the temperature is the most suitable for practical applications, which directed that Cu0.75Zn0.25S thin film is suitable for solar cell applications.